2011
DOI: 10.1002/ajmg.b.31220
|View full text |Cite
|
Sign up to set email alerts
|

Genome scan of age‐at‐onset in the NIMH Alzheimer disease sample uncovers multiple loci, along with evidence of both genetic and sample heterogeneity

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disorder of late life with a complex genetic basis. Although several genes are known to play a role in rare early-onset AD, only the APOE gene is known to have a high contribution to risk of the common late-onset form of the disease (LOAD, onset > 60 years). APOE genotypes vary in their AD risk as well as age-at-onset distributions, and it is likely that other loci will similarly affect AD age-at-onset. Here we present the first analysis of age-at-onset in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 72 publications
8
18
0
Order By: Relevance
“…The main region identified in our sample on chr 6 overlaps a region reported previously for AAO in the independent NIMH AD dataset analyzed alone (Choi et al 2011; Dickson et al 2008) or together with other samples (Holmans et al 2005) (Table III). This region of overlap is not at the position with the strongest previously-reported linkage statistic in the NIMH AD sample, but represents a secondary location at ~110 cM, with evidence for linkage to this position driven by a subset of the sites contributing to the NIMH AD sample (Choi et al 2011).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The main region identified in our sample on chr 6 overlaps a region reported previously for AAO in the independent NIMH AD dataset analyzed alone (Choi et al 2011; Dickson et al 2008) or together with other samples (Holmans et al 2005) (Table III). This region of overlap is not at the position with the strongest previously-reported linkage statistic in the NIMH AD sample, but represents a secondary location at ~110 cM, with evidence for linkage to this position driven by a subset of the sites contributing to the NIMH AD sample (Choi et al 2011).…”
Section: Discussionsupporting
confidence: 78%
“…The strongest evidence for linkage, to chr 6q, overlaps a previously reported region for an AAO locus in samples that included the NIMH AD dataset (Choi et al 2011; Dickson et al 2008; Holmans et al 2005) (Table III), and therefore provides the first independent confirmation in a different sample of an AAO locus in this region. The region on chr 19q13.42 is explained by the well-established APOE locus, and was noted in an earlier analysis of a subset of this sample (Wijsman et al 2004) as well as in several previous genome scans of AAO in other samples (Choi et al 2011; Dickson et al 2008; Holmans et al 2005; Li et al 2002), all of which included at least part of the NIMH AD sample. The families used in the current sample provided a dataset that is suitable for identifying loci contributing to AAO because of the large sample size, the high proportion of large families, the ascertainment on a large number of subjects with confirmed autopsies, and the relatively complete age information in both affected subjects and unaffected subjects.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…14 Subsequent genome-wide linkage scans examining AAO in AD patients and unaffected family members (using age at study entry) found suggestive evidence of linkage on chromosome 19 to APOE (LOD = 3.28), 15 which was confirmed in later studies. 16 Multiple studies identified other suggestive linkage signals on chromosomes 4q, 8q, 16 1q, 6p, 17 7q, 15, and 19p 18 in Caucasian families, and chromosomes 5q, 7q, 14q, and 17q 19 in Caribbean Hispanics, though the specific loci driving these linkage signals remain unknown. More recently, an AAO GWAS in 2,222 Caucasian AD cases confirmed association at APOE , and also found strong evidence of association ( P =4.95×10 −7 ) on chromosome 4q31.3 in the gene DCHS2 .…”
Section: Introductionmentioning
confidence: 99%